Manufactures, King County and Machinery Buildings, Alaska-Yukon-Pacific-Exposition, Seattle, Washington, 1909 - University of Washington Libraries. Special Collections Division (1909)
Caption on image: X76. Manufacturers, King County and Machinery Hall. Official Post Card. Printed on verso: Portland Post Card Co. Seattle, Wn., and Portland, Ore. PH Coll 777 PPCC.76a (See also PH Coll 78.82 and PH Coll 433.41) To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number